ANTIBIOTIC SUSCEPTIBILITY PATTERN OF VIBRIO PARAHAEMOLYTICUS ISOLATED FROM RETAIL SEAFOODS IN MYSORE - RAKSHA AJITPRASAD MANIYANKODE; JOSEPH JEYABALAJI KINGSTON; PUJA SHARMA; HARSH VARDHAN BATRA (International Journal of Pharma and Bio Sciences, 2013)
The present work was aimed to evaluate the antimicrobial resistance pattern in Vibrio parahaemolyticus isolates from seafoods. A total of 56 V. parahaemolyticus isolates could be recovered and identified from various seafoods sold at retail shops of Mysore and they were tested for their sensitivity against 27 antibiotics of varied nature. About 3.6% of these isolates were found to possess the virulent associated genes, tdh and trh. MAR index analysis illustrated resistance between 0.00- 0.52 and among these 26.8% were multiple drug resistant. The bacterial strains were predominantly resistant to Oxacillin and Pencillin (≥ 72%), while no resistance was observed against Ceftriaxone, Norfloxacin, Ciprofloxacin, oloxacin, Streptomycin, Gentamycin, Neomycin and Amikacin. In conclusion, significant numbers of V. parahaemolyticus strains were found to be resistant to antibiotics commonly used as therapeutic agents, feed supplement and growth promoters, indicating a need for supervised use of antibiotics and of frequent surveillance of judicious V. parahaemolyticus strains for antimicrobial resistance.